Smoked and Fermented Bushmeat (Mpunam) Products: Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) Resulting From Processing - A. S. Amponsah; H. E. Lutterodt; G. M. Ankar-Brewoo; I. W. Ofosu (International Journal of Food Science)
The polycyclic aromatic hydrocarbons (PAHs) congener concentrations and risk upon human exposure to smoked bushmeat products were analyzed. GC/MS MRM and QuEChERS methods were used for the analysis. This work has become necessary due to the need for more information concerning the quantitative determination of these compounds and their health risk assessment. The 16 PAH congeners identified were acenaphthylene (ACA), naphthalene (NAP), acenaphthene (ACE), fluorene (FLU), anthracene (ANT), phenanthrene (PHE), fluoranthene (FLT), pyrene (PYR), benzo[b]fluoranthene (BBF), benzo[k]fluoranthene (BKF), benzo[a]anthracene (BAA), chrysene (CHR), indeno(1,2,3-cd)pyrene (IND), dibenzo(a,h)anthracene (DAA), benzo(g,h,i)pyrene (BGP), and benzo[a]pyrene (BAP). At the 5% and 95% daily intake levels, BAP was at 3.34 and 17.39 μg/kg(bw)/day, ΣPAH4 was at 25.11 and 109.15 μg/kg(bw)/day, and ΣPAH8 was at 55.76 and 236.68 μg/kg(bw)/day, respectively. BAP, ΣPAH4, and ΣPAH8 concentration exceeded the European Union limits, as BAP concentration was as low as 6.09 μg/kg and as high as 34.19. The exposure values were significantly high. Specifically, the margin of exposure for BAP was as low as 2.09×10−2; for ΣPAH4, it was 1.36×10−−2; and for ΣPAH8, it was 1.95×10−2 all at the 95% level. These figures are substantially lower than the benchmark of 10,000, indicating a higher ILTCR. Furthermore, the ILTCR ranged from a minimum of 47.77 to a maximum of 248.53 at the 5% and 95% levels, respectively. This study makes smoked bushmeat a public health concern because the higher figures obtained indicate higher carcinogenicity upon consumption.